2012
DOI: 10.4236/fns.2012.37121
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure Differs between Black and White Americans: Implications for Obesity Prevention Research

Abstract: Objective: To assess differences in energy expenditure by race and ethnicity using nationally representative data. Results: We confirmed that Blacks exhibit lower resting energy expenditure than Whites—a difference of approximately 150 to 300 fewer kilocalories per day. This finding was significant in each permutation of our analysis—from the simple association of race and resting energy expenditure to our final regression model adjusted for common confounders (i.e. age, gender, income, and education), body fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…1,7,37 In addition, the prediction and comparability of body composition data across studies and different body composition models/ methods poses challenges, particularly in racially diverse, resource-limited settings. 21,38,39 To our knowledge, this is the first study in (South) Africa that includes such a population and sample size objectively measuring REE. We took into account sex, age, body composition and height when determining race/ethnicity differences in measured REE.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,7,37 In addition, the prediction and comparability of body composition data across studies and different body composition models/ methods poses challenges, particularly in racially diverse, resource-limited settings. 21,38,39 To our knowledge, this is the first study in (South) Africa that includes such a population and sample size objectively measuring REE. We took into account sex, age, body composition and height when determining race/ethnicity differences in measured REE.…”
Section: Discussionmentioning
confidence: 99%
“…Anthanont and Jensen 40 found that adults with low, compared to those with high, basal metabolic rates did not gain more weight, thereby concurring with the earlier review of Luke et al, 41 who argued that increased weight gain among Black individuals is unlikely to be related to lower REE. Nonetheless, Amen-Ra et al 21 and at least the move towards personalised nutrition in clinical settings 1 suggest accounting for related factors, including race/ethnicity, when considering an energy prescription for the management of obesity. It is hoped that our new equation will serve this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations